DO HUMAN RESOURCES ACCOUNTING DISCLOSURE DETER INVESTORS' DECISIONS IN THE BANKING SECTOR? - Sundari, Siti; Hidayat, Widi; Isnalita; Nuswantara, Dian Anita; Run, Pharatt (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
A different perspective of management and shareholders may cause conflict that hampers long-term organizational objectives. Human Resources Accounting (HRA) as an element of long-term investment has become more prevalent as information that deters investor decisions. This study enlarges shareholder theory that focuses on HRA disclosure as voluntary disclosure. The quantitative approach using PLS-SEM provides empirical evidence that HRA disclosure mediates the relationship between firm size-firm value and profitability-firm size in a negative direction. The mediation form of HRA disclosure on profitability's effect on firm value is full mediation. Q2 of 25.2% indicates that the Firm's Size, profitability, and HRA disclosure can explain the variation in the firm's value change by 25.2%. Therefore, future research should include other variables that affect the firm's value, including NPL, CAR, and company age. This finding contributes to revisiting voluntary disclosure theory by questioning the theory. And give additional evidence from the signaling theory perspective that the voluntary one failed to send a good signal to the receiver.